2019
DOI: 10.17159/2310-3833/2019/vol49n3a5
|View full text |Cite
|
Sign up to set email alerts
|

Visual motor integration delay in preschool children infected with HIV

Abstract: Human Immunodeficiency Virus (HIV) causes a chronic condition that impacts the immune system resulting in infections and lifelong dependence on medication for survival. The growth and health as well as the economic and food security, psychosocial care, education and family composition of children with the virus are also affected 1. The estimated number of children living with HIV globally in 2018 was 2.1 million 2 and at the time, it was estimated that 260 000 of these children (aged 0 to 14) were living in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The literature reported conflicting information regarding the impact of gender on VMI [52][53][54][55][56]. The literature was at a consensus that diagnosis impacts VMI [66][67][68][69][70]. Specifically, ASD, BPI, and CP are associated with VMI deficits [16,[58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature reported conflicting information regarding the impact of gender on VMI [52][53][54][55][56]. The literature was at a consensus that diagnosis impacts VMI [66][67][68][69][70]. Specifically, ASD, BPI, and CP are associated with VMI deficits [16,[58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a negative impact on VMI skills in children with primary stereotypic movement disorder [70]. Overall, the literature was at a consensus that diagnosis impacts VMI skills [66][67][68][69][70]. Table 6 provides a summary of the findings.…”
Section: Occupational Therapy Internationalmentioning
confidence: 98%
See 2 more Smart Citations